Creating Entrepreneurs through Vocational High School to Reduce Unemployment in Indonesia - Citra Marcella Nazira; Lindawati Kartika (International Journal of Entrepreneurship, Business, and Creative Economy, 2021)
In many nations, including Indonesia, unemployment is one of the key problems. the percentage rate of unemployment in Indonesia is still relatively high compared to other countries, although it has dropped every year. Vocational High School (VHS) graduates dominate the largest number of unemployed individuals in Indonesia. Creative entrepreneurs are one option since they can build their own work. But the entrepreneurial interest of VHS students in Indonesia is still low. The objective of this research is to develop strategies for creating entrepreneurship in conjunction with the skills needed to become entrepreneurs. Primary data was gathered with eleven headmasters of VHS in Indonesia through focus group discussion (FGD) and secondary data collected from literature research. The data analysis was processed through stakeholder analysis and the house model to create an effective strategy and decision. The study results indicate that synergistic cooperation from a quadruple helix consisting of universities, entrepreneurial societies, government, and industry is required in order to achieve 'one student, one business' mission as the output. Furthermore, organizing talent management to provide the mindset as CEO for vocational students and training school principals is a way out of this issue in order to create links and match VHS student interests and providing the growth of CEO mindset training for the VHS principals. Therefore, VHS Students can establish their own company and become entrepreneurs according to their interests and ambitions, both before and after graduating from VHS.